Cryptosporidiosis occurrence in HIV+ patients attended in a hospital, Brazil - Paulo César Ribeiro; Edwin Pile; Margareth Maria de Carvalho Queiroz; Antonio Neres Norberg; José Ricardo de Oliveira Tenório
Cryptosporidiosis occurrence was determined in HIV+ patient assisted in the Clinic of Infect-parasitic Diseases in a hospital of Nova Iguaçu, Rio de Janeiro, Brazil, in the period from Juy/1998 to March/1999. In order to research, seventy-five patient, carriers of diarrhea or not, were appraised. The samples of feces were collected and placed in saline solution with formaldehyde (5%). The Modified Ritchie technique was used for the oocysts research, and the smears were stained with Safranine O methylene blue. The results verified 9.33% of positive samples, with higher frequency of cases in patients of the masculine sex from 20 to 50 years old, however without significant difference.